Structural Characterization of Lignin in Four Cacti Wood: Implications of Lignification in the Growth Form and Succulence - Reyes-Rivera, Jorge; Soto-Hernández, Marcos; Canché-Escamilla, Gonzalo; Terrazas, Teresa (Frontiers in Plant Science, 2018)
Wood lignin composition strongly depends on anatomical features and it has been used as a marker for characterizing major plant groups. Wood heterogeneity in Cactaceae is involved in evolutionary and adaptive processes within this group; moreover, it is highly correlated to the species growth form. Here we studied the lignin structure from different types of woods in four Cactaceae species with different stem morphologies (Pereskia lychnidiflora, tree/fibrous wood; Opuntia streptacantha and Pilosocereus chrysacanthus, tree/succulent fibrous wood; Ferocactus hamatacanthus, cylindrical stem/dimorphic wood) in order to determine their relationship with the wood anatomy in an evolutionary-adaptive context. Dioxane lignin was isolated and analyzed by pyrolysis coupled with gas chromatography and mass spectrometry (Py-GC/MS), two-dimensional nuclear magnetic resonance spectroscopy (2D-NMR) and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The main linkages are the β–O–4′ ether (67-85%), the β–β' resinol (10-26%) and the β–5′ and α–O–4′ linkages of the phenylcoumaran structures (≤ 7%). Spirodienone structures have a considerable abundance (5%) in the dimorphic wood of F. hamatacanthus. In addition, low contents (≤ 3%) of α,β-diaryl ether, α-oxidized β–O–4′ ether and dibenzodioxocin structures were found. The sinapyl- and coniferyl acetates are not part of the wood lignin in any of the studied species. The low (≤ 5%) γ-acetylation in the F. hamatacanthus and P. chrysacanthus wood lignin is here interpreted as an evidence of a high specialization of the wood elements in the conduction/storage of water. The lignin of the studied Cactaceae is composed predominantly of guaiacyl and syringyl units (S/G: 0.9-16.4). High abundance of syringyl units (62-94%) in three of the four species is considered as a defense mechanism against oxidative agents, it is a very conspicuous trait in the most succulent species with dimorphic wood. Furthermore, it is also associated with ferulates and the herein called γ-acetylated guaiacyl-syringaresinol complexes acting as nucleation sites for lignification and as cross-links between lignin and carbohydrates at the wide-band tracheid-fiber junctions.